Information Retrieval with the Help of Geographic Information Systems – Key Competency for Modern Geo-Communication - Volz, Daniel; Viehrig, Kathrin; Siegmund, Alexander (Journal of Geography Education, 2010)
Digital geo-information is already an important resource for many jobs and every day life. Through initiatives such as INSPIRE, its presence will grow even more in the years to come. Consequently, many curricula for secondary education mandate students to learn how to use geographic information systems (GIS), the key technological basis for dealing with digital geo-information. This paper reviews current research and theoretical considerations regarding the competencies needed for retrieving information with the help of GIS, as well as some of their cognitive foundations, as a basis for building a competency model.